Effect of stroke early supported discharge on length of hospital stay: analysis from a national stroke registry - Sarah Lewis (BMJ Publishing Group, 2021)
Objective The first observational study to investigate the impact of early supported discharge (ESD) on length of hospital stay in real-world conditions.Design Using historical prospective Sentinel Stroke National Audit Programme (SSNAP) data (1 January 2013–31 December 2016) and multilevel modelling, cross-sectional (2015–2016; 30 791 patients nested within 55 hospitals) and repeated cross-sectional (2013–2014 vs 2015–2016; 49 266 patients nested within 41 hospitals) analyses were undertaken.Setting Hospitals were sampled across a large geographical area of England covering the West and East Midlands, the East of England and the North of England.Participants Stroke patients whose data were entered into the SSNAP database by hospital teams.Interventions Receiving ESD along the patient care pathway.Primary and secondary outcome measures Length of hospital stay.Results When adjusted for important case-mix variables, patients who received ESD on their stroke care pathway spent longer in hospital, compared with those who did not receive ESD. The percentage increase was 15.8% (95% CI 12.3% to 19.4%) for the 2015–2016 cross-sectional analysis and 18.8% (95% CI 13.9% to 24.0%) for the 2013–2014 versus 2015–2016 repeated cross-sectional analysis. On average, the increased length of hospital stay was approximately 1 day.Conclusions This study has shown that by comparing ESD and non-ESD patient groups matched for important patient characteristics, receiving ESD resulted in a 1-day increase in length of hospital stay. The large reduction in length of hospital stay overall, since original trials were conducted, may explain why a reduction was not observed. The longer term benefits of accessing ESD need to be investigated further.Trial registration number http://www.isrctn.com/ISRCTN15568163.